2014
DOI: 10.2196/mhealth.3262
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Usability of a Mobile App for Adolescent Obesity Management

Abstract: BackgroundObesity is a global epidemic. Behavioral change approaches towards improving nutrition, increasing physical activity level, improving sleep, and reducing sitting time are recommended as best practices in adolescent obesity management. However, access to evidence-based treatment is limited and portable technologies such as mobile apps may provide a useful platform to deliver such lifestyle interventions. No evidence-based validated app exists for obesity intervention; therefore, a novel mobile app (Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 21 publications
1
43
0
4
Order By: Relevance
“…14 By adapting face-to-face overweight and obesity treatment, smartphone interventions have the potential to encourage small, but significant, health behavioral changes. 21 The multimodal and interactive nature of Webbased technologies, including smartphone applications, can capture personal relevance and motivation via broad opportunities for feedback, offer individual choices for learning and literacy styles, and provide a diversity of interactive components capable of matching specific behavioral change goals. 22 This systematic review provides a comparative evaluation of the effectiveness of smartphones in multidisciplinary treatment of childhood obesity in the last 5 years, with a specific interest in behavior change.…”
Section: Introductionmentioning
confidence: 99%
“…14 By adapting face-to-face overweight and obesity treatment, smartphone interventions have the potential to encourage small, but significant, health behavioral changes. 21 The multimodal and interactive nature of Webbased technologies, including smartphone applications, can capture personal relevance and motivation via broad opportunities for feedback, offer individual choices for learning and literacy styles, and provide a diversity of interactive components capable of matching specific behavioral change goals. 22 This systematic review provides a comparative evaluation of the effectiveness of smartphones in multidisciplinary treatment of childhood obesity in the last 5 years, with a specific interest in behavior change.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown the importance of usability testing for successful app development. [57][58][59] The thinkaloud method has proven to be a useful way to gain insight into the thought processes and problems of test persons, especially in digital health interventions. 31 58 In order to apply the results of the usability test, a process evaluation is included in the study, in which usage data of the app, as well as obstacles during app use, will be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Questionnaire design was inspired by the research described in the paper "Exploring the Usability of a Mobile App for Adolescent Obesity Management" by O'Malley et al 10 Questionnaire included 15 questions where the majority of it was a multiple choice. It was divided into four parts and the estimated time for its completion was 5 min.…”
Section: Questionnaire Designmentioning
confidence: 99%